Efficient palm vein authentication encryption technique in wireless implantable medical devices - Ahlam Almukhlifi; Saad M. Almutairi (Institute of Advanced Engineering and Science, 2023)
Implantable medical devices (IMD) are commonly utilized to treat chronic illnesses. Many IMD communicate in wireless mode using an external programmer, which raises security concerns. Security of IMD is a critical issue which assaults direct harm to patients. Many researches are carried out on IMD security and challenges when the patient is not in a critical situation. Still, it would be a major issue while the patient is unconscious. In this research, a novel scheme for emergency secure access control of IMD was proposed to improve the security of biometric-based IMD schemes. The proposed authentication scheme uses a combination of palm vein and zero-watermark to generate encrypted credential data for IMDs. Using quantitative assessment for evaluating images, such as the peak signal-to-noise ratio (PSNR), structural similarity index (SSIM), and the mean squared errors (MSE), the suggested framework is shown to be superior to existing methods. Two other study goals are improved efficiency and image quality at a lower computational cost.